Open-Circuit Voltage (VOC) Enhancement in TiO2-Based DSSCs: Incorporation of ZnO Nanoflowers and Au Nanoparticles - Borbón Rojas, Susana; Lugo Loredo, Shadai; Pourjafari Nokandeh, Dena; Pineda Aguilar, Nayely; Oskam, Gerko; López, Israel (American Chemical Society, 2020)
An important reason for the relatively low efficiency of dye-sensitized solar cells (DSSCs) is the low open-circuit voltage (VOC) of about 0.7 V for a standard solar cell with a dye that has an absorption onset at 1.6 eV. We report an enhancement of the VOC of about 0.10 V with respect to a TiO2-based DSSC modified with ZnO nanoflowers that we prepared by a new and facile method. An additional increase of the VOC of about 0.08 V was achieved by modifying the ZnO nanoflowers with Au nanoparticles, resulting in a DSSC with an efficiency of 2.79%, highlighted by a high VOC of 0.89 V. Detailed analysis with electrochemical impedance spectroscopy and intensity-modulated photovoltage and photocurrent spectroscopies (IMVS and IMPS) reveal that the main reason for the increase of VOC is related to the shift of the band edges upon coupling TiO2 with ZnO nanoflowers, even though the electron lifetime at the same charge density actually decreases. These results show the intricate interplay between band edge shift, recombination kinetics, and DSSC performance and illustrate that a higher voltage DSSC can be fabricated by modification of the photoanode materials.